Estudo da hidrólise e fermentação de resíduos de milho (zea mays) para produção de etanol de segunda geração - Carvalho, Lívia Luísa Melo de (2016)
in the current context of searches for Bioproducts from renewable sources and the concern with environmental conditions makes biofuels, which are produced from biomass, an alternative to the global dependence on petroleum products. In this way, there is a growing appreciation of wastes from agro-industry as a source of lignocellulosic feedstock for ethanol 2 g (second-generation ethanol). In this sense, the aim of this study was to evaluate the steps of hydrolysis and fermentation of straw and hydrolytic stock corn cob for second-generation ethanol production, testing various process conditions. For this purpose, the corn residues were pretreated with 0.5% H2SO4 at 121ºc for 15 minutes in enzymatic hydrolysis tests in table rotating type incubator shaker to 50ºc and 150rpm, using 20FPU/mL of enzyme Cellic Ctec 2 ®, varying the load of biomass hydrolysis time and type of biomass according to the experimental planning, which made the study of the best operation conditions of hydrolysis through observation of the effects and combinations of parameters, where the best ART index (g/L) was for straw with 5 g of biomass for 48 hours getting 30, 68 g/L, in the range investigated. Fermentation was conducted in shaker to 30ºc, 200 rpm for 24 hours with 90.97% fermentation efficiency, obtaining 3, 9 g/L of alcohol.